Impulsive Cluster Anticonsensus of Discrete Multiagent Linear Dynamic Systems - Liping Zhang; Haibo Jiang (Discrete Dynamics in Nature and Society)
Cluster anticonsensus is another important type consensus of multiagent systems. In this paper, we investigate the problem of impulsive cluster anticonsensus of discrete multiagent linear dynamic systems. Firstly, an impulsive protocol is designed to achieve the cluster anticonsensus. Then sufficient conditions are given to guarantee the cluster anticonsensus of the discrete multiagent linear dynamic system based on the Q-theory. Numerical simulation shows the effectiveness of our theoretical results.